Cinema brasileiro no começo do século XXI : tensão entre violência e alteridade na representação da periferia - Carias, Felipe Biguinatti (2023)
National cinema, at the dawn of the new millennium, saw an innovative intervention in the industry with regard to the interaction between the public and the malls. However, to what extent has the market cooled the political and social debate on works? The present research aims to analyze four works from the beginning of the 21st century through immanent film analysis for Ismail Xavier and Luiz Costa Lima’s reception theory to try to understand the atmosphere, according to Gumbrecht, of the time. When analyzing Chronically Unfeasible (2000), by Sérgio Bianchi; The Trespasser (2002), by Beto Brant; City of God (2002), by Fernando Meirelles and Kátia Lund and Madame Satã (2002), Karim Aïnouz, we found the constancy and concern of understanding urban violence in light of the mutual relationship between social atomization and the breakdown of violence. Neoliberalism, based on differentiated aesthetics, legitimizes this interaction in the characters' daily lives. In a certain way, because of this, in almost all films studied, there is an interaction between crime and capitalism, sometimes through Zé Pequeno's drug trafficking management in City of God, sometimes through Anísio's metamorphosis in The Trespasser. The industry, despite its direct interference, did not cool down the political debate in the works, on the contrary, directors discovered that they absorbed commercial aesthetics to talk to the public and from there formulate hypotheses to interpret a period as violent as the beginning of the 21st century and the boom of multinationals around the globe.